Identification the Level of Social Vulnerability of the Tsunami Disaster in the Coastal Area of Bengkulu City, Indonesia - Mayasari, Zulfia Memi; Bertham, Yudhi Harini; Farid, Muhammad; Hadi, Arif Ismul (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
This study investigates the spatial dynamics of social vulnerability to tsunami hazards in Bengkulu City by applying the BNPB (2012) framework as a national reference for index-based assessments. Five key social indicators: population density, gender ratio, poverty, disability, and age were analyzed using spatial techniques and secondary socio-demographic data to identify spatial disparities in vulnerability across sub-districts. The findings reveal that Teluk Segara and Ratu Samban Sub-Districts are the most socially vulnerable areas, driven not only by high population density and poverty but also by their low-lying coastal topography, direct exposure to the Indian Ocean, and limited evacuation accessibility. In contrast, inland sub-districts such as Selebar and Singaran Pati demonstrate lower vulnerability levels due to their higher elevation and greater distance from the coast. These spatial variations indicate that social vulnerability in Bengkulu City is strongly influenced by the interaction between socio-economic vulnerability and oceanographic conditions. The study emphasizes the importance of integrating social and oceanographic dimensions into tsunami risk assessments to better reflect site-specific realities and support more effective mitigation planning.  Teluk Segara and Ratu Samban Sub-Districts need to be a priority for targeted preparedness efforts, improved evacuation infrastructure, and the restoration of coastal ecosystems is essential to reduce tsunami impacts. The results contribute to advancing integrated coastal disaster risk management in Indonesia by reinforcing the need to link human vulnerability with coastal environmental processes to achieve sustainable and resilient coastal communities.